Equivalence in rendering imagery in Shakespeare{u2019}s Sonnets in the translations of Esmat Wali & Mohamed Enani - Ayman Bakr Ibrahim Aly; Hoda Shukry Ayad (Cairo : Ayman Bakr Ibrahim Aly, 2020)
Poetry translation is one of the thorny issues in the field of translation studies, taking into account the stylistic features, rich imagery, and indirect expression of meanings that poetry usually entails. Furthermore, this issue gets more complex when it comes to the translation of the iconic Shakespearean sonnets. The present thesis attempts to examine the translation, or rather rendering, of imagery in Shakespeare{u2019}s sonnets by Esmat Wali and Mohamed Enani. The study aims at tracking the mechanisms of the decision-making process of both translators in transferring the imagery of Shakespeare{u2019}s sonnets into Arabic, and to explore the strategies used by each of them to convey the underlying layers of meanings throughout the sonnets. Equivalence stands for the methodological tool, according to which the TTs are analyzed to figure out the level(s) of equivalence each TT either succeeds in or fails to realize. This present study is a descriptive, product-oriented descriptive translation study, as it mainly focuses on analyzing the translation of imagery in the TTs. In addition, the analytical part of the thesis addresses representative samples of imagery in the sonnets, as it focuses analysis on 31 sonnets, where images and their rendering into the TTs are remarkable, indicative, and valuable for the purpose of the study. The theory of equivalence in translation, as presented by several translation theorists and scholars, is adopted as the methodological framework of the study. The analysis does not adopt a specific definition or classification of equivalence, but rather applies any type of equivalence, whenever it fits. Therefore, this paper aims at finding out and discussing how far each translator approaches, by means of the translational techniques and strategies, imagery in the sonnets, in order to convey both the aesthetic and semantic values that lie behind and within the imagery of the original sonnets
Thesis (M.A.) - Cairo University - Faculty of Arts - Department of English
Issued also as CD
Keywords: Imagery; Poetry; Shakespeare